Utero-vaginal prolapse in far western region of Nepal - Pant, PR (Journal of Institute of Medicine Nepal, 2010)
Background: Utero-vaginal prolapse (UVP) is very common among Nepalese women. There are about 600,000 patients suffering from this gynaecological condition, amongst which 200, 00 require immediate correction. UVP is multifactorial and results in weakening of pelvic support, connective tissue and muscles as well as nerve damage. Methods: Prospective, descriptive study, conducted in the Far-western region vaginal hysterectomy camp from 14th to 29th April2009. Result: Of 325 women with UVP, 45.54 % were Biswakarmas, 38.08% Brahmin, 17.23% Chhetri, 5.23% Tharu and 0.92 5 from other communities. Early return to work (within 10 days of delivery) among Biswakarma and Brahmin was 95.27 % and 91.09% respectively where as smoking and chronic cough in Biswakarma and Chhetri was 92.57%, 66.22% and 78.56%, 34.4 % respectively. Conclusion: Early return to work, smoking and chronic cough are major contributors of UVP in far western Nepal which is more prevalent in the Biswakarma community. Key words: Utero-vaginal prolapse, UVP, contributing factors. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, August, 2009; 31:2 19-21